Simple Techniques for Antegrade Guiding Catheter Engagement after Retrograde CTO Crossing - Gregor Leibundgut; Angelo Quagliana; Florian Riede; Heinz-Joachim Büttner (Journal of Interventional Cardiology)
Interventional treatment of chronic total occlusions (CTOs) is nowadays counting on a wide span of procedural possibilities, and retrograde approaches are becoming more and more frequent as they warrant high success rates at the cost of a slightly higher incidence of donor vessel damage. Retrograde lesion crossing needs to be followed by procedural conversion to an antegrade approach to dilate and stent the lesion, and new techniques are being proposed to address this issue and achieve a safer recanalization of the vessel. In this context, we propose novel and simple techniques to antegrade guiding catheter engagement by the retrograde wire, enhancing the chances for procedural success.